Catalytic conditions of fucoidan degrading enzymes from Vasticardium flavum - Khanh, Huynh Hoang Nhu; Trang, Vo Thi Dieu; Thinh, Pham Duc; San, Pham Trung (Vietnam Journal of Science and Technology, 2019)
The fucoidanase from the digestive glands of the marine shell Vasticardium flavum was studied. The fucoidanase catalysed the hydrolysis of 1→3-L-fucan from sea cucumbers Stichopus variegatus, Holothuria spinifera, did not catalyze the hydrolysis of fucoidan from F. evanescens and F. vesiculosus containing alternating α-1→4 and α-1→3 glycoside bonds. This enzyme also did not catalyze the hydrolysis of fucoidan from U. pinnatifida, S. mcclurei, which belong to the galactofucan group. Optima of pH and time incubation were at 3-4 and 24 hours, respectively. The enzyme activity was significantly increased in the presence of the Ca2+, Ba2+, Co2+ and Mg2+ cations, but the Cu2+, Sn2+, Fe2+ and Al3+ cations partially inactivated the enzyme. The enzyme was completely inactivated after 5 min of incubation at 65° C.